The positive effect of water on photo-induced step transfer-addition & radical-termination (START) polymerization. Issue 29 (24th March 2017) - Xu, Tianchi; Zhang, Lifen; Cheng, Zhenping; Zhu, Xiulin
Abstract : In photo-induced Step Transfer-Addition & Radical-Termination (START) polymerization, the addition of water greatly enhanced the overall polymerization efficiency and inhibited the function loss (C–I). Abstract : Step-growth radical copolymerization between α, ω-diiodoperfluoroalkanes (A ) and α, ω-unconjugated dienes (B ) proceeds efficiently through a photo-induced Step Transfer-Addition & Radical-Termination (START) strategy in aqueous/organic biphasic system. The addition of water in our polymerization strategy enhanced the overall polymerization efficiency and inhibited the function loss (C–I) significantly, which has been illustrated through UV-vis tests. Therefore, most of the functional groups (C–I) in the polymer chain end have been preserved in the final polymer product (AB ) n based on 19 F NMR analysis. After polymerization, we could erase the iodine atoms in the main chain of (AB ) n, which generates semifluorinated polyolefins with enhanced thermal stability.